Synthesis of polyfunctionalized benzo[d]thiazoles as novel anthranilic acid derivatives. Issue 27 (1st July 2015) - Hédou, Damien; Harari, Marine; Godeau, Julien; Dubouilh-Benard, Carole; Fruit, Corinne; Besson, Thierry
Graphical abstract: Synthesis of versatile polyfunctionalized benzothiazoles as relevant molecular platforms for the synthesis of innovative heterocyclic systems. Highlights: Synthesis of novel polyfunctionalized benzo[ d ]thiazoles was performed. An interesting thermal versus Cu mediated cyclization is clearly demonstrated. Heating was efficiently realized under microwaves. Abstract: A small library of valuable novel polyfunctionalized benzo[ d ]thiazole derivatives was prepared in a straightforward and convenient manner. Here again, 4, 5-dichloro-1, 2, 3-dithiazolium chloride (Appel salt) proved to be an efficient agent for merging a 2-cyanothiazole ring to an arene counterpart.